Тил дарсларида интерфаол усуллардан фойдаланишнинг максад ва вазифалари. - Adilova, S (FILOLOGIYA UFQLARI JURNALI, 2021)
This article deals with the use of interactive teaching methods on the history of their appearance and on the principles of vibration of these methods based on the specifics of the topic.